Lines of distinction: self-other dynamics within cultural groups - Knaus, Julia (2019)
Lines of Distinction establishes a critical framework for the study of relationship dynamics within cultural groups. As a critical framework, Lines of Distinction are differences associated with value judgements that determine what and who is considered ‘self,’ and therefore ‘good,’ or ‘other,’ and therefore ‘bad.’ This is applied to the often unexamined interior dynamics of cultural groups, using the English-speaking Sherlock Holmes fandom as a primary case study.